Odpowiedź :
Hej!
A)
-3xy - (2x - y + 2xy) =
= -3xy - 2x + y - 2xy =
= -5xy - 2x + y
B)
4ab + (2a - 3ab) =
= 4ab + 2a - 3ab =
= ab + 2a
C)
-(3p - r) - 2r =
= -3p + r - 2r =
= -3p - r
D)
-st - (-2t + s) =
= -st + 2t - s
E)
4 - (m + 5 - n) =
= 4 - m - 5 + n =
= -m + n - 1
F)
4g - (-2h + g - 3) =
= 4g + 2h - g + 3 =
= 3g + 2h + 3
Pozdrawiam! - Julka
A) -3xy-(2x-y+2xy) = -3xy - 2x + y - 2xy = -5xy - 2x + y
B) 4ab+(2a-3ab) = 4ab + 2a - 3ab = ab + 2a
C) -(3p-r)-2r = -3p + r - 2r = -3p - r
D) -st-(-2t+s) = -st+ 2t - s
E) 4-(m+5-n) = 4 - m - 5 + n = -1 - m + n
F) 4g-(-2h+g-3) = 4g + 2h - g + 3 = 3g + 2h + 3